Nation Branding of Kepulauan Riau Through Subregional Cooperation in The Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT) - Rizqi Apriani Putri; Ella Afnira (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2024)
Nation branding has become a key element in modern communication strategies, particularly in the context of globalization. Countries strive to establish a positive international image, reflecting their unique identity and values. Nation branding is a marketing and communication strategy aimed at enhancing a country’s image, both domestically and globally. Kepulauan Riau participation in the Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT) cooperation, and its hosting of the IMT-GT event in 2023, represents an effort to strengthen its image internationally. The IMT-GT is a subregional economic collaboration involving Indonesia (Sumatra), Malaysia, and Thailand, with the Kepulauan Riau being an active participant. This research utilizes a descriptive-analytical approach, supported by secondary data, to examine the impact of this initiative. One of the notable implementations of this cooperation is the IMT-GT Expo